Butein Inhibits Angiogenesis of Human Endothelial Progenitor Cells via the Translation Dependent Signaling Pathway. (6th June 2013) - Chung, Ching-Hu; Chang, Chien-Hsin; Chen, Shiou-Sheng; Wang, Hsueh-Hsiao; Yen, Juei-Yu; Hsiao, Che-Jen; Wu, Nan-Lin; Chen, Yen-Ling; Huang, Tur-Fu; Wang, Po-Chuan; Yeh, Hung-I; Wang, Shih-Wei
Abstract : Compelling evidence indicates that bone marrow-derived endothelial progenitor cells (EPCs) can contribute to postnatal neovascularization and tumor angiogenesis. EPCs have been shown to play a "catalytic" role in metastatic progression by mediating the angiogenic switch. Understanding the pharmacological functions and molecular targets of natural products is critical for drug development. Butein, a natural chalcone derivative, has been reported to exert potent anticancer activity. However, the antiangiogenic activity of butein has not been addressed. In this study, we found that butein inhibited serum- and vascular endothelial growth factor- (VEGF-) induced cell proliferation, migration, and tube formation of human EPCs in a concentration dependent manner without cytotoxic effect. Furthermore, butein markedly abrogated VEGF-induced vessels sprouting from aortic rings and suppressed microvessel formation in the Matrigel implant assay in vivo . In addition, butein concentration-dependently repressed the phosphorylation of Akt, mTOR, and the major downstream effectors, p70S6K, 4E-BP1, and eIF4E in EPCs. Taken together, our results demonstrate for the first time that butein exhibits the antiangiogenic effect both in vitro and in vivo by targeting the translational machinery. Butein is a promising angiogenesis inhibitor with the potential for treatment of cancer and other angiogenesis-related diseases.